SOSIALISASI GERAKAN MASYARAKAT CERDAS MENGGUNAKAN OBAT DI DESA KUMAIN KECAMATAN TANDUN KABUPATEN ROKAN HULU - Asiska Permata Dewi; Isna Wardaniati; Denia Pratiwi; May Valzon (LPPM Universitas Abdurrab, 2019)
Has been done community service about dagusibu (get, use, save, and dispose) drugs correctly in Kumain Village, Rokan Hulu District, Riau. This activity is aimed to improve people's understanding in the use of drugs and is a joint effort between lecturers and the community in order to realize awareness, understanding, and community skills in using medicine properly and correctly. Minister of Health of the Republic of Indonesia on November 13, 2015 proclaimed